Burden of diarrhea in the Eastern Mediterranean region, 1990-2015: findings from the Global Burden of Disease 2015 study - Khalil, Ibrahim; Jonas, Jost B.; Mohammed, Shafiu (International journal of public health, 2017)
Diarrheal diseases (DD) are an important cause of disease burden, especially in children in low-income settings. DD can also impact children’s potential livelihood through growth faltering, cognitive impairment, and other sequelae.
Gesehen am 23.04.2020